Manajemen Penerimaan Peserta Didik Baru (PPDB) Jalur Prestasi Dalam Peningkatan Prestasi Siswa di SMP Negeri 1 Jetis Ponorogo - Endang Setyowati; Fata Asyrofi Yahya (Edumanagerial, 2023)
The admission of new students (Penerimaan Peserta Didik Baru/PPDB) is the first step of educational institutions in their efforts to improve the quality of education by producing excellent students. One of the interesting paths of PPDB is the achievement path, in this case students who have achievements at the SD/MI/equivalent level can register in the achievement path, where this achievement can be utilized to continue to be developed. The research was conducted using a qualitative method with a case study research type. PPDB planning for achievement pathways in improving student achievement at SMP Negeri 1 Jetis includes conducting a selection of superior prospective students, forming a PPDB committee, determining the capacity of students, making announcements of new student recruitment, planning for the selection of new students, planning for the orientation of new students, planning for the placement of students, and finally there is recording and reporting from planning. Meanwhile, the implementation of achievement pathway PPDB in improving student achievement at SMP Negeri 1 Jetis is carried out by applying four elements that go hand in hand, namely coordination and communication related to the implementation of PPDB and management of follow-up to achievement pathway PPDB, motivation from superiors and decision making. For the supervision of PPDB achievement pathways in improving student achievement at SMP Negeri 1 Jetis, it is carried out by applying elements that go hand in hand, namely monitoring from superiors, then evaluations from all parties concerned and there is also reporting as a form of accountability. The success of achievement pathway PPDB management in improving student achievement is determined by four indicators, namely the motivation of new students on the achievement pathway, the increase in academic achievement, the increase in non-academic achievement, and the existence of a school routine in the form of achievement Monday as a form of school appreciation.